Avaliação da resposta imunológica de cães portadores de Leishmaniose tratados com extrato seco de noni (Morinda citrifolia) - BATISTA, Zulmira da Silva (2014)
Visceral leishmaniasis (VL) is a anthropozoonosis worldwide distribution that affects humans, canines and marsupials. The disease is caused by different species of protozoa of the genus Leishmania and is transmitted by the bite of sand flies insects. The dog has been appointed as the main host and reservoir of LV, being probably the most important natural reservoir related to human cases. Moreover, it has a key role in the expansion of the disease in endemic areas. This study aimed to evaluate the cytokine profile, hematological and biochemical dogs with Leishmania infantum and treated with dry extract of Morinda citrifolia. For this study, nine dogs of both sexes and various breeds were used. Screening of animals was given through the ELISA / S7® testing and detection of parasites in blood smears. Animals used in the studies were all symptoms. To conduct the survey EDTA blood for complete blood count and blood without EDTA to carry out the biochemical and cytokines were collected. Tissue was also harvested in ear for conducting histopathological and immunohistochemical examinations. The following clinical variables was evaluated: hypertrophy of popliteal lymph nodes, skin changes, onychogryphosis, cachexia and eye injuries. Regarding clinical signs was observed that 78% had lymphadenopathy, 67% had skin lesions; 55% had hepatosplenomegaly, 44% had been slimming 33% presence of ocular lesions. While determining the hematologic values was statistically significant (p ≤ 0.05) in the values of MCV and platelet count. For the evaluation of the biochemical significance was (p = 0.05) for serum ALT, AST, urea and creatinine. Regarding cytokine assay no significant statistical result. The histopathological examination demonstrated decreased inflammation. And the examination of immunohistochemical not demosntrated presence of the parasite. Thus, it appears that studies of the differences in the cytokine profile in dogs presenting the most diverse forms of symptoms of CVL are inconclusive, since the results are contradictory.